Complex Involvement of the Extracellular Matrix, Immune Effect, and Lipid Metabolism in the Development of Idiopathic Pulmonary Fibrosis - Qian, Weiping; Xia, Shu; Yang, Xiaoyun; Yu, Jiaying; Guo, Bingpeng; Lin, Zhengfang; Wei, Rui; Mao, Mengmeng; Zhang, Ziyi; Zhao, Gui; Bai, Junye; Han, Qian; et al. (Frontiers in Molecular Biosciences, 2022)
Background and objective: Idiopathic pulmonary fibrosis (IPF) is an aggressive fibrotic pulmonary disease with spatially and temporally heterogeneous alveolar lesions. There are no early diagnostic biomarkers, limiting our understanding of IPF pathogenesis. Methods: Lung tissue from surgical lung biopsy of patients with early-stage IPF (n = 7), transplant-stage IPF (n = 2), and healthy controls (n = 6) were subjected to mRNA sequencing and verified by real-time quantitative PCR (RT-qPCR), immunohistochemistry, Western blot, and single-cell RNA sequencing (scRNA-Seq). Results: Three hundred eighty differentially expressed transcripts (DETs) were identified in IPF that were principally involved in extracellular matrix (ECM) remodeling, lipid metabolism, and immune effect. Of these DETs, 21 (DMD, MMP7, POSTN, ECM2, MMP13, FASN, FADS1, SDR16C5, ACAT2, ACSL1, CYP1A1, UGT1A6, CXCL13, CXCL5, CXCL14, IL5RA, TNFRSF19, CSF3R, S100A9, S100A8, and S100A12) were selected and verified by RT-qPCR. Differences in DMD, FASN, and MMP7 were also confirmed at a protein level. Analysis of scRNA-Seq was used to trace their cellular origin to determine which lung cells regulated them. The principal cell sources of DMD were ciliated cells, alveolar type I/II epithelial cells (AT cells), club cells, and alveolar macrophages (AMs); MMP7 derives from AT cells, club cells, and AMs, while FASN originates from AT cells, ciliated cells, and AMs. Conclusion: Our data revealed a comprehensive transcriptional mRNA profile of IPF and demonstrated that ECM remodeling, lipid metabolism, and immune effect were collaboratively involved in the early development of IPF.